The Relation of the SHBG Gene Polymorphism (rs1799941) with PCOS in a Group of Iraqi Women - Hisham, Rusul; Shehab, Adel Fawzy; Omair, Hadeel Abdel-Hadi (Journal for Research in Applied Sciences and Biotechnology, 2022)
Polycystic Ovary Syndrome (PCOS) is the most common and complex endocrine disorder that affects women of childbearing age. However, the causes of PCOS are still unknown, however, there is strong evidence supporting the role of genetics in causing it, because PCOS has a strong familial predisposition. More than one gene contributes to the heterogeneous phenotype and clinical and biochemical presentation. Patients with PCOS may complain of irregular menstruation, unwanted hair growth in multiple areas of the body, acne and scalp hair loss, unexplained weight gain, and infertility. This study explores the polymorphism of the SHBG gene locus (rs1799941) in Iraqi women with PCOS that may cause the onset of this disease. Genomic DNA was extracted from blood samples of women with and without PCOS. The SHBG gene was amplified by Tetra_ARMS PCR technology, after which the PCR product was migrated onto the agarose jells at a concentration of 2%. Three genotypes appeared, the homozygous (normal) homozygous GG which is represented by (404 + 270 bp) genotype, the heterozygous (GA) which is represented by (404 + 270 + 210) bp and the homozygous mutant AA genotype. (Which is represented by the bundle (404 + 210 bp). Among the 70 women with PCOS included in the molecular study, (4) of them were carriers of the normal homozygous genotype GG, (44) of them were carriers of the heterozygous genotype GA and (22) were carrying the mutated genotype AA. In the current study, the (OR) value of the mixed GA genotype appeared (12.833) and this indicates that the mixed genotype is a risk factor for the disease, while the (OR) value of the AA mutant genotype was (9.250), and this indicates that the mutant genotype is Homozygous is a risk factor for the disease. The frequency of the A allele was higher in the infection group compared to the control group, and this indicates that the A allele is responsible for the disease association. These results indicated that the locus SHBG gene polymorphism (rs1799941) is associated with PCOS in Iraqi women.